2008
DOI: 10.1530/eje-07-0692
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and adiponectin concentrations in intrauterine growth restricted and appropriate for gestational age fetuses, neonates, and their mothers

Abstract: Objective: Leptin and adiponectin are two adipocytokines that play a critical role in the control of energy balance and metabolism as well as in conditions, such as insulin resistance, inflammation, and the development of the metabolic syndrome in adult life. Leptin has been associated with asymmetric intrauterine growth restriction (IUGR). The aim of this study was to investigate the perinatal implication of leptin and adiponectin in IUGR. Design: Leptin and adiponectin were measured in the plasma of 40 mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 61 publications
3
72
1
3
Order By: Relevance
“…In obese pregnant women, the concentrations of fasting glucose, insulin, and leptin at 16 weeks' gestation resemble those in the third trimester of nonobese, nondiabetic pregnant women (13,14). Moreover, obesity is associated with a higher proportion of the major bacterial phylum Actinobacteria and a lower proportion of the phylum Tenericutes.…”
Section: Discussionmentioning
confidence: 98%
“…In obese pregnant women, the concentrations of fasting glucose, insulin, and leptin at 16 weeks' gestation resemble those in the third trimester of nonobese, nondiabetic pregnant women (13,14). Moreover, obesity is associated with a higher proportion of the major bacterial phylum Actinobacteria and a lower proportion of the phylum Tenericutes.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in the past, we have shown that the mothers of babies with intrauterine growth restriction share a common metabolic feature with their offspring, i.e. increased circulating leptin levels, compared with mothers of babies of normal growth (32).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Apart from being expensive, laboratories at majority of centers are not equipped with facilities of measurements of these markers. Measurement of maternal serum ferritin has also been used as a predictive marker of increase risk of IUGR.…”
Section: Introductionmentioning
confidence: 99%